2005
DOI: 10.1099/vir.0.80573-0
|View full text |Cite
|
Sign up to set email alerts
|

Pig anelloviruses are highly prevalent in swine herds in France

Abstract: A survey of anelloviruses in swine herds from Britanny, France, is reported. By using PCR targeted to the conserved untranslated region, prevalences of 93 and 73 % were found among 15 herds and 33 animals, respectively. The lung was the organ found to be positive most frequently among the five organs tested from 32 animals. The highest identity levels of our nucleotide sequences were found with pig isolates from Japan and with an isolate from Tupaia belangeri. Interestingly, when aligning all available swine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
64
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 20 publications
6
64
1
1
Order By: Relevance
“…The high occurrence of TTV infection (20-73%) observed in these pigs agrees with results previously reported (Leary et al 1999, Bigarré et al 2005. Such a high prevalence can be explained by the containment conditions that facilitates transmission (Deng et al 2000, Gerner et al 2000, Martínez-Guinó et al 2009) and the ubiquitous characteristic of TTV.…”
Section: Discussionsupporting
confidence: 80%
“…The high occurrence of TTV infection (20-73%) observed in these pigs agrees with results previously reported (Leary et al 1999, Bigarré et al 2005. Such a high prevalence can be explained by the containment conditions that facilitates transmission (Deng et al 2000, Gerner et al 2000, Martínez-Guinó et al 2009) and the ubiquitous characteristic of TTV.…”
Section: Discussionsupporting
confidence: 80%
“…Relatively little is known about the clinical significance of TTV infection. TTV is ubiquitous in pigs worldwide (48)(49)(50). While TTV is commonly detected in healthy pigs, several studies have suggested that TTV infection moderates disease severity during coinfections.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, TTSuV2 was detected in all pSE (100%, 8/8) at 14 days of age but showed a reduced value of 62.5 (5/8) at 30 days of age; however, the virus was detected in all pSE (100%, 8/8) [3][4][5][6][7][8] in more than one sampling times and showed consecutive PCR positivity in at least 2 sampling ages. On the contrary, 62.5% (5 out of 8) of pSE were TTSuV2 PCR positive (No.…”
mentioning
confidence: 90%
“…On the contrary, 62.5% (5 out of 8) of pSE were TTSuV2 PCR positive (No. [3][4][5][6]8) at all sampling ages while none of the pSE was TTSuV2 PCR negative throughout the study period. All pSE (100%, 8/8) were TTSuV2 PCR positive in more than one sampling age and showed PCR positive in at least 2 consecutive sampling ages.…”
mentioning
confidence: 99%
See 1 more Smart Citation